2006
DOI: 10.1212/01.wnl.0000208501.52849.dd
|View full text |Cite
|
Sign up to set email alerts
|

A novel locus for hereditary spastic paraplegia with thin corpus callosum and epilepsy

Abstract: Two consanguineous families with complicated autosomal recessive hereditary spastic paraplegia were clinically characterized and genetically mapped to a new locus on 8p12-p11.21.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 24 publications
3
37
0
Order By: Relevance
“…These white matter changes have been reported before in the literature. 9,10,17,20 Loss of volume (thinning) and agenesis of the corpus callosum were seen in 10 out of 18 (55.5%) patients. Involvement of the corpus callosum was the second most common abnormality found by MRI in our patients.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…These white matter changes have been reported before in the literature. 9,10,17,20 Loss of volume (thinning) and agenesis of the corpus callosum were seen in 10 out of 18 (55.5%) patients. Involvement of the corpus callosum was the second most common abnormality found by MRI in our patients.…”
Section: Discussionmentioning
confidence: 98%
“…21 Epilepsy was noted in 13 (17.5%) of our patients; 3 of them had a thin corpus callosum. 9,10 Different types of seizures have been associated with HSP. 5,21 In the current study, tonic-clonic seizures were found in 7 children, myoclonic in 4, and partial in two.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations